2014
DOI: 10.1371/journal.pone.0088780
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Muscle Findings May Be Essential for a Definitive Diagnosis of Suspected Sharp Trauma Associated with Ship Strikes in Stranded Cetaceans

Abstract: Ship strikes are a major issue for the conservation of may cetacean species. Certain gross and microscopic criteria have been previously reported for establishing a diagnosis of death due to ship strikes in these animals. However, some ship-strike injuries may be masked by advanced carcass decomposition and may be undetectable due to restricted access to the animals. In this report we describe histopathological muscular findings in 13 cetaceans with sharp trauma from ship strikes as the cause of death. Skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 36 publications
5
25
0
Order By: Relevance
“…Histopathologic lesions observed in some propeller strike cases (discoid and segmental disintegration of myofibers) were consistent with lesions observed in experimentally traumatized skeletal muscle exposed to seawater (Stacy et al 2015) and with those reported in large whales by Sierra et al (2014), indicating that perimortem propeller injuries can be identified in whale carcasses even when wounds have been washed out by seawater. In fact, the study by Stacy et al (2015) illustrated that seawater exposure increases detectability of discoid and segmental disintegration in muscle injuries caused during the perimortem/supravital period.…”
Section: Traumatic Lesionssupporting
confidence: 83%
“…Histopathologic lesions observed in some propeller strike cases (discoid and segmental disintegration of myofibers) were consistent with lesions observed in experimentally traumatized skeletal muscle exposed to seawater (Stacy et al 2015) and with those reported in large whales by Sierra et al (2014), indicating that perimortem propeller injuries can be identified in whale carcasses even when wounds have been washed out by seawater. In fact, the study by Stacy et al (2015) illustrated that seawater exposure increases detectability of discoid and segmental disintegration in muscle injuries caused during the perimortem/supravital period.…”
Section: Traumatic Lesionssupporting
confidence: 83%
“…The rhabdomyolysis and haemorrhage in the neck and pectoral muscles of drowned penguins, without lesions in the adjacent subcutaneous tissue, may have resulted from exertional myopathy or agonal movements. Previous studies demonstrated the value of histopathology and histochemistry to differentiate muscular lesions from autolysis on stranded cetaceans (Sierra et al 2014), and in this study we found that PTAH histochemistry was particularly helpful to confirm the occurrence of rhabdomyolysis (see Fig. 2c,d).…”
Section: External Lesions and Skeletal Musclessupporting
confidence: 67%
“…For the diagnosis of traumatic intra-interspecific interactions we took a conservative approach based on previous references (5,6,37) excluding the cases in which other possible traumatic causes of death such as fisheries interaction, vessel collision, or a live stranding (38)(39)(40)(41)(42) could not be ruled out. Stress-related lesions were histologically studied in selected samples upon availability [skeletal muscle (n = 24), lung (n = 23), cardiac muscle (n = 21), liver (n = 19), kidney (n = 19), and adrenal gland (n = 14)].…”
Section: Methodsmentioning
confidence: 99%